Brain Mechanisms Underlying Visuo-Orthographic Deficits in Children With Developmental Dyslexia - Cao, Fan; Yan, Xin; Spray, Gregory J.; Liu, Yanni; Deng, Yuan (Frontiers in Human Neuroscience, 2018)
Multiple hypotheses have been proposed to explain the reading difficulty caused by developmental dyslexia (DD). The current study examined visuo-orthographic processing in children with dyslexia with a focus on whether orthographic deficits are explainable solely by visual deficits. To identify the orthographic-specific, visual perception-specific, and overlapped deficits, we included two tasks (lexical and perceptual) in three subject groups: children with DD, age-matched controls (AC), and reading matched controls (RC). We found that the left precuneus showed decreased activation across both tasks for the DD group compared to the two control groups, thus reflecting visual processing deficits in children with DD, which also affects orthographic processing. Furthermore, we also found that the functional connectivity between left middle occipital gyrus (LMOG) and left inferior frontal gyrus (IFG) decreased in DD compared to AC and RC only in the lexical task, suggesting a weaker association between orthography and phonology for DD. The DD group also showed decreased connectivity between the LMOG and right parahippocampal gyrus only for the visual perceptual task, indicating a weaker association between the visual cortex and the subcortical memory network for DD during visual symbol processing. Taken together, our findings suggest that the orthographic processing deficit in DD might be driven by both a basic visual deficit and a linguistic deficit.